1999
DOI: 10.1111/j.1699-0463.1999.tb01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological findings and value of placental examination at fetal and perinatal autopsy

Abstract: The purpose of this study was to report on the morphological findings in placentae from abortions, stillbirths and perinatal deaths, and to assess the value of the results of the placental examinations. The material included 341 placentae and their matched autopsies. Fifty placentae came from abortions induced for medical reasons, 194 from spontaneous abortions, 84 from stillbirths, and 13 from livebirths. Histological slides from all placentae were reviewed and the placental diagnoses were related to the auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The placental findings associated with stillbirth have been evaluated in a number of studies (8-15). In most of these, there was no control group so the authors could not determine the true association of placental pathology to stillbirth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The placental findings associated with stillbirth have been evaluated in a number of studies (8-15). In most of these, there was no control group so the authors could not determine the true association of placental pathology to stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the complex pathogenic interplay between the mother, fetus and placenta that leads to stillbirth has generally focused on maternal and fetal disorders (4-7). Examination of placental pathology to elucidate its contribution to stillbirth has been limited by insufficient sample size, lack of appropriate controls, ill-defined nomenclature, and non-standardized placental examination protocols (8-15). Thus, we sought to compare macroscopic and microscopic abnormalities of the umbilical cord, membranes, and placenta in singleton stillbirths and live births, both overall and within groups defined by gestational age at delivery, in a large, multisite, population-based case-control study with a standardized placental examination protocol.…”
Section: Introductionmentioning
confidence: 99%
“…51 Cases with positive placental findings at perinatal autopsy range from 30% to 61%. [52][53][54][55][56][57] Chorioamnionitis is the most common placental lesion associated with cerebral palsy in term and preterm infants. [58][59][60] Fetal thrombotic vasculopathy may be present.…”
Section: Placentamentioning
confidence: 99%
“…In the third trimester, the overall proliferation rate for the trophoblasts falls to nearly 10% of the first trimester value (Castellucci and Kaufmann, 2000). In spontaneous abortions, the trophoblasts are less hyperplastic (van Lijnschoten et al, 1994) and degenerative lesions are frequently found in the placental tissue (Larsen and Graem, 1999;Benirschke and Kaufmann, 2000). Therefore, trophoblasts from the placentas of normal pregnancies, abortions, and cases of intrauterine death, and from tissue samples from cases of GTD, seem to differ in terms of their respective rates of proliferation and degeneration.…”
Section: Introductionmentioning
confidence: 99%